1990
DOI: 10.1007/bf01311289
|View full text |Cite
|
Sign up to set email alerts
|

Immunological characterization of the Marin County strain of astrovirus

Abstract: Marin County virus (MCV) was isolated from a stool suspension and serially propagated in human embryonic kidney cell cultures. MCV particles in stool and cell-propagated virus stocks showed reactivity by immune electron microscopy (IEM) with rabbit antiserum to astrovirus type 5. MCV antigen was also detected in two MCV stool samples by enzyme immunoassay (EIA) with an astrovirus group-specific monoclonal antibody. Acute and convalescent sera from 3 of 3 MCV-infected patients showed seroconversion to cell-prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…A fourfold response to HAst-1, 1/20 (acute phase)-1/80 (convalescent phase) was demonstrated by immunofluorescence in a volunteer challenged with HAst-5. Similar responses were previously demonstrated by IEM and RIA [6,12].…”
Section: Serological Response Following Human Infectionsupporting
confidence: 89%
See 2 more Smart Citations
“…A fourfold response to HAst-1, 1/20 (acute phase)-1/80 (convalescent phase) was demonstrated by immunofluorescence in a volunteer challenged with HAst-5. Similar responses were previously demonstrated by IEM and RIA [6,12].…”
Section: Serological Response Following Human Infectionsupporting
confidence: 89%
“…Pre-and post-challenge sera were obtained from an adult volunteer (DA) infected with a faecal extract derived from material obtained from the original outbreak which occurred in California in 1978 [13]. Subsequent studies identified the causative agent as astrovirus type 5 [6,10,15]. All sera had been stored at -20 C.…”
Section: Hast-4; London Uk November 1982mentioning
confidence: 99%
See 1 more Smart Citation
“…Astroviruses are currently classified into seven antigenic types, HAstV-1 to HAstV-7, on the basis of immune EM and immunofluorescence techniques (18)(19)(20) using polyclonal and monoclonal antibodies (10) to cell culture-adapted virus. Epidemiologic studies using EM (2,16,21,22,30,40) and the more recently developed enzyme immunoassays (EIAs) (3,9,11,12,17,23,28,29,33) have demonstrated the worldwide distribution of astroviruses.…”
mentioning
confidence: 99%
“…Indeed, samples from three of the other four sick rabbit from the same outbreak tested negative for the virus (Table 1). Nevertheless, astroviruses cause gastroenteritis in other mammals, and it is possible that this virus caused or exacerbated the illness in a subset of the animals [13,24,25,28,29,47]. The coccidian parasites and bacteria evident in the samples may have also contributed to the enteritis and from this data alone, it is impossible to ascertain whether this astrovirus is capable of causing disease.…”
Section: Discussionmentioning
confidence: 99%